Pupils’interactions and decision-making in an educational game - Senja Celius; Fredrik Rusk; Wenche Rønning (Education Inquiry)
By way of video observations, the current article examines the social interaction of pupils playing an educational card game about fractions, focusing on their epistemic and deontic negotiations during decision-making in dyads. Our findings reveal recurring patterns in how pupils make decisions, emphasising the importance of both epistemic (knowledge-based) and deontic (rights-based) negotiations. Additionally, pupils often struggle to anticipate and manage resistance from peers when negotiating decisions. When resistance occurs, the interaction shifts from negotiating the basis of knowledge (epistemics) to negotiating the right to determine future actions (deontics). The implications of these findings highlight the need for structured support in educational games to foster more productive learning interactions.